Study on the effectiveness of commercial available voltage regulator / Asri Anuar - Anuar, Asri (2002)
Protecting solid-state electronic equipment from AC power line disturbances is a growing concern. Computers are subjected to data errors, crashing, and are sometimes damaged or destroyed by voltage transients as a result of an absence or misapplication of protective devices. Due to the important role that voltage regulators play in the electric power systems stability and the present limited information about models and parameters representative of their dynamic behaviour, it has become necessary to study, analyze and establish a basic methodology to test these regulators in order to obtain the performance and effectiveness of voltage regulator. This project concerns on test of voltage regulation limit, the time response, the operating voltage, corresponding between input and output, and the regulated operation. The effectiveness and performance of voltage regulator system is studied and analyzed.